Colloids in one dimensional random energy landscapes - Hanes, Richard; Dalle-Ferrier, Cecile; Schmiedeberg, Michael; Jenkins, Mathew; Egelhaaf, Stefan (Soft Matter, 2012)
Individual colloidal particles have been studied experimentally in a one dimensional random potential with energies that follow a Gaussian distribution. This rough, noise-like potential has been realised using a holographic optical set-up, which allows the width of the distribution to be varied. For different widths, the particle trajectories were followed and the particle dynamics characterised by, for example, the mean square displacement, non-Gaussian parameter, van Hove function, time-dependent diffusion coefficient and residence time distribution. The values obtained for these observables are consistent with the static properties of the system, in particular the barrier height distribution, which was obtained by a detailed characterisation of the tweezer-like set-up. The dynamics display three distinct behaviours: at short times normal diffusion, subsequently an extended regime of localisation within the different minima of the potential and finally a very slow approach towards long-time diffusive behaviour, for which diffusion coefficients consistent with theoretical predictions have been found.